Thermo-responsive chiral column by scissoring motion from rigid–flexible aromatic rod assembly. (January 2016) - Chen, Shen; Deng, Danfeng; Xie, Siying; Wu, ShanShan; Peng, Jing; Ma, Cong; Xu, Ping; Tang, Dongyan; Wu, Xiaohong; Huang, Zhegang
Graphical abstract: Highlight: Multiplying stacking introduce thermo-responsive chirality through scissoring motion. Abstract: Here, we report thermo-responsive chiral columns from self-assembled coil-rod-coil molecules. The rigid rods self-assemble into multiplying dimers which stack on the top of one another to form non-chiral columnar crystal. Notably, the achiral crystal transforms into 2D hexagonally ordered liquid crystal with supramolecular chirality as heating. The reversible chiral switching behavior within columnar structures arises from scissoring motion from neighbored molecules driven by high thermal entropy of flexible chains relative to stiff-rod.